Global Map of Specialized Metabolites Encoded in Prokaryotic Plasmids - Saati-Santamaría, Zaki (Microbiology spectrum, 2023)
Plasmids are the main mobile elements responsible for horizontal gene transfer (HGT) in microorganisms. These replicons extend the metabolic spectrum of their host cells by carrying functional genes. However, it is still unknown to what extent plasmids carry biosynthetic gene clusters (BGCs) related to the production of secondary or specialized metabolites (SMs). Here, we analyzed 9,183 microbial plasmids to unveil their potential to produce SMs, finding a large diversity of cryptic BGCs in a few varieties of prokaryotic host taxa. Some of these plasmids harbored 15 or more BGCs, and many others were exclusively dedicated to mobilizing BGCs. We found an occurrence pattern of BGCs within groups of homologous plasmids shared by a common taxon, mainly in host-associated microbes (e.g., Rhizobiales, Enterobacteriaceae members). Our results add to the knowledge of the ecological functions and potential industrial uses of plasmids and shed light on the dynamics and evolution of SMs in prokaryotes. IMPORTANCE Plasmids are mobile DNA elements that can be shared among microbial cells, and they are useful for bringing to fruition some microbial ecological traits. However, it is not known to what extent plasmids harbor genes related to the production of specialized/secondary metabolites (SMs). In microbes, these metabolites are frequently useful for defense purposes, signaling, etc. In addition, these molecules usually have biotechnological and clinical applications. Here, we analyzed the content, dynamics, and evolution of genes related to the production of SMs in >9,000 microbial plasmids. Our results confirm that some plasmids act as a reservoir of SMs. We also found that some families of biosynthetic gene clusters are exclusively present in some groups of plasmids shared among closely related microbes. Host-associated bacteria (e.g., plant and human microbes) harbor the majority of specialized metabolites encoded in plasmids. These results provide new knowledge about microbial ecological traits and might enable the discovery of novel metabolites.
Keywords: Multigene Family; plazmidy; sekundární metabolismus; Bacteria; Secondary Metabolism; Plasmids; secondary metabolism; lidé; multigenová rodina; megaplasmids; Humans; plasmids; microbial ecology